Courting an intervention: conceptualising the judicial role in matters relating to section 139 of the South African constitution - Franklyn, Claire Susan (University of the Witwatersrand, Johannesburg, 2024)
This Thesis conceptualises the developing judicial role in matters relating to section 139 of the South African Constitution, being the constitutional intervention mechanism in terms of which a provincial executive (or, in certain circumstances, the national executive) intervenes, temporarily and in a circumscribed manner, in a dysfunctional municipality. The burgeoning judicial role has developed within the context of systemic local government collapse, persistent service delivery failures, and failing and dysfunctional constitutional accountability and intergovernmental monitoring and support mechanisms. Three broad categories of section 139 intervention matters are identified in this Thesis: first, the judicial review of a decision to initiate a section 139 intervention, second, the judicial review of a failure to take such a decision, and third, a catch-all category relating to matters which trigger, or at least, this Thesis argues, should trigger, a consideration of section 139 of the Constitution, where such intervention does not form part of the requested relief. Chapter 1 sets out the policy, constitutional and legal framework and practice of the section 139 intervention mechanism. Chapter 2 draws on case law and academic literature relating to the South African court’s adjudication of different subject matters (or ‘streams’), each of which have elements pertaining to the section 139 intervention mechanism, to develop a conceptual, analytical and evaluative framework for constructing a judicial role conception in matters relating to section 139 of the Constitution. Chapters 3, 4 and 5 apply this framework to systematically analyse the case law falling within the three identified categories of section 139 intervention matters, tracing doctrinal developments and building a conception of the judicial role with a focus on justiciability, judicial scrutiny and remedial prescriptiveness. The conclusion to the Thesis in Chapter 6 consolidates insights from the three categories, ultimately arguing that the South African environment is generally conducive to litigation relating to section 139 of the Constitution, with the court adopting a catalytic judicial role, shifting its levels of judicial scrutiny and remedial prescriptiveness in each category based on an intersection of its understanding of its own role under the doctrine of separation of powers, the role of governmental action and responsiveness, the integrity and healthy functioning of the applicable democratic institutions, structures and processes, and the seriousness of any underlying socio-economic rights violations.
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy to the Wits School of Law, Faculty of Law, Commerce and Management, School of Law, University of the Witwatersrand Johannesburg 2024
Keywords: SECTION 139 OF THE CONSTITUTION; MUNICIPAL DYSFUNCTION; MANDATORY INTERVENTION; DISCRETIONARY INTERVENTION; UCTD; SDG-8: Decent work and economic growth